2015
DOI: 10.1016/j.apm.2015.01.052
|View full text |Cite
|
Sign up to set email alerts
|

A fuzzy railroad blocking model with genetic algorithm solution approach for Iranian railways

Abstract: Please cite this article as: M. Yaghini, M. Momeni, M. Sarmadi, M. Seyedabadi, M.M. Khoshraftar, A fuzzy railroad blocking model with genetic algorithm solution approach for Iranian Railways, Appl. Math. Modelling (2014), doi: http://dx. AbstractIn the railway, the fright car classification takes place in the terminals. This classification always imposes a remarkable delay to the movement of the cars from origin to destination. To reduce car handling, it is necessary to group various shipments together with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Since the TFP for railway freight transportation is at the tactical level (medium term, e.g. one month or even one year) [14], it may not be appropriate at the operational level. Hence, it is necessary to adjust the train formation plan during the actual operation according to the real-time transportation demands and other special cases, e.g., natural disasters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the TFP for railway freight transportation is at the tactical level (medium term, e.g. one month or even one year) [14], it may not be appropriate at the operational level. Hence, it is necessary to adjust the train formation plan during the actual operation according to the real-time transportation demands and other special cases, e.g., natural disasters.…”
Section: Discussionmentioning
confidence: 99%
“…A simulated annealing based heuristic algorithm was developed to solve the model. Other studies include the ant colony optimization algorithm [12], tabu search [13], genetic algorithm [14], etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, regions with limited capacity, where the number of cars and equipment capacity of a shunting yard is limited, use the minimum dwell time of cars at the station as the objective function [6]. Yaghini [4] proposed a railway blocking model with fuzzy travel costs for railway freight costs and transformed it into a classic railway blocking model. The results showed that the method could significantly reduce the costs of transporting goods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Beloevi [5] studied the reorganization of freight trains at technical stations and trains marshalling methods, and according to the scale of the complexity of different grouping tasks, the rational application of the elementary grouping plan, triangle grouping plan and geometric grouping plan was proposed. Although [4][5] have achieved promising results, their studies were conducted at a single technical station, and the cooperation between technical stations was neglected. This may have prevented the car-flow organization of railway freight trains from being optimized at the railway network level and increased the total cost of railway freight transportation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation